Penilaian Maturity Level Perangkat Lunak Menggunakan CMMI-Dev 1.3 pada Aplikasi Manans MINT - Yumma Yustika Asmy; Leonardi Paris Hasugian (Jurnal Manajemen Informatika (JAMIKA), 2021)
The purpose of this study was to determine the Maturity Level achievement of the Manans MINT application from the software assessment process using CMMI-Dev 1.3 the extent to which application software development supports Manan's Farm business process activities. Capability Maturity Model Integration was chosen because it is an approach that provides important elements to improve company performance. Research aids in analyzing data use PIECES to identify and classify problems with the current system. The research method uses qualitative and quantitative descriptive writing techniques. In this study, Staged Representation is used as a process of grouping areas and RACI Chart to determine the appropriate respondents. The final result of this research is the calculation of Maturity Level results with recommendations for process improvement of the Manans MINT application software. Manans MINT is in mature position 2, namely Managed. The average condition of the readiness level for the calculation of Generic Practices has the required proportion and has been applied at 85%. Meanwhile, the maturity level of Specific Practices for REQM and PMC process areas is 90% and 72.5%, respectively. This research become the basis for improving the work system of the Manans MINT application so that the successful goal of building Manan's Farm can be achieved.